Mia measures up - Simon, Coco; West, Tracey, 1965- (Simon, Coco. Cupcake diaries, 2017)
Reaching a compromise with her parents when they say she is too young to attend a concert alone, Mia discovers that she is being cyberbullied on social media and teams up with her fellow Cupcake Club members to discover who is behind the attacks.